Antibacterial Agent from Ninhydrin - LASKAR, S.; KUNDU, P.; SEN, S.K. (Asian Journal of Chemistry, 2010)
Ninhydrin, a well known reagent for both the detection and quantitative estimation of amino acids, is a non-bioactive compound against some bacterial organisms. On heating with concentrated sulfuric acid-nitric acid mixture (1:1; v/v) for prolonged period on water bath, ninhydrin gave a compound which showed high activity against some bacterial organisms (Bacillus subtilis, Escherichia coli and Salmonella sp.). Infrared spectral analysis, 1H NMR study and ultimate X-ray studies showed the prepared compound was phthalic acid.